Participatory crop improvement for farm productivity and climate resilience: Training manual - Mengistu, Dejene K.; Terefe, Hailu; Nigir, Bogale; Tilahun, Mulugeta; Kidane, Yosef G.; Fadda, Carlo (2025)
The challenge of feeding the growing population under the current changing climate is most difficult especially for the subsistent farming systems. These systems are characterized by incredible diversity, not of crops alone, but of micro-environments, socio-economic contexts, and cultural preferences. For decades, conventional plant breeding, optimized for uniform, high-input environments, has struggled to serve this heterogeneity, leading to low adoption rates of improved varieties and missed opportunities for enhancing food security. This manual presents a paradigm shift: a move from a top-down, transfer-of-technology model to a collaborative, farmer-centric approach to crop improvement. We detail an integrated framework that synergistically combines three powerful participatory methods: Participatory Variety Selection (PVS), Evolutionary Plant Breeding (EPB), and Crowdsourcing (Tricot), supported by the digital platform ClimMob. This framework is not merely about evaluating varieties; it is about building a decentralized, adaptive, inclusive learning system and end users empowerment for agricultural innovation. Empirical evidence from across the globe demonstrates that this approach delivers tangible impacts:  Accelerates genetic gain: Reduces the variety evaluation cycle from a decade or more to just 2-3 years.  Enhances adoption & Equity: Increases adoption rates by 30-50% by ensuring varieties align with farmer preferences, with specific gains among women and marginalized farmers.  Builds climate resilience: Generates location-specific recommendations and develops dynamically evolving populations that buffer against climate shocks.  Strengthens seed systems: Creates robust feedback loops between formal research and informal seed networks, enhancing both the supply of and demand for adapted varieties. This manual is a practical guide. It provides step-by-step protocols, ethical frameworks, advanced statistical foundations, in-depth case studies, and ready-to-use templates. It is designed for practitioners seeking to make crop improvement more relevant, rapid, and resilient.